Association of Body Mass Index with the Severity of SARS-COVID-19 Pneumonia in Hospitalized Patients - Zafar, Zara; Alamgir, Wasim; -Humayun, M. Zill-e; Rehman, Aayesha; Ain, Qurat Ul; Ilyas, Sumaira (Pakistan Armed Forces Medical Journal, 2023)
Objective: To determine the association of body mass index with the severity of COVID-19 pneumonia in hospitalized patients.Study Design: Cross-sectional study.Place and Duration of Study: Pak Emirates Military Hospital, Rawalpindi Pakistan, form May to Jun 2021.Methodology: Patients diagnosed with COVID-19 pneumonia on PCR and chest imaging and admitted to our hospital were included in the study. Body mass index was calculated on the first day of hospital admission, and they were followed up for two weeks during the disease. Increased oxygen demand, duration of admission, CT severity score and use of non-invasive ventilation were compared in patients with normal and increased body mass index.Results: A total of 800 COVID-19 patients admitted to the hospital were included in the final analysis. The mean age of the study participants was 41.36±4.55 years. Out of 800 patients, 337(42.1%) had normal BMI, 420(52.5%) were classed in the category of overweight and 43(5.4%) were obese. Furthermore, it was seen that increased demand for oxygen, high CT severity score and longer duration of hospital admission had a statistically significant relationship (p-value